Avaliação de lesões e traumas ósseos por meio de termografia infravermelha - Strasse, Wally Auf Der (2022)
Bone fractures are considered common orthopedic trauma in hospital orthopedic departments. According to their severity, the diagnosis may evolve favorably or present recurrent bone infections and a prognosis of pseudarthrosis, being in this case a public health problem due to the long clinical treatment. The evaluation of of the healing process by means of X-ray and Computed Tomography imaging technologies exposes patients to frequent doses of ionizing radiation that are cumulative and harmful to health, in addition to the high cost of exams. Bone repair is directly related to metabolic changes, which present thermal changes due to the increase or decrease in blood flow around the lesion. The objective of the present study was to analyze the feasibility of thermography as a non-invasive diagnostic method and clinical follow-up in bone healing and the establishment of thermal cut-off between normal ranges and the diagnoses of tibial pseudarthrosis, chronic osteomyelitis and bone tumor. This is a prospective study, composed of 886 participants, 222 patients and 664 healthy individuals of different ethnicities, body composition, ages and genders composing the reference thermal profile. The study was carried out in different hospitals in the city of Curitiba, in the municipality of São José dos Pinhais – Paraná and in hospitals in Porto, Portugal. Thermographic images were acquired in the same positioning as the X-ray, with the Flir T-530 camera in acute trauma and in the phases of bone formation, remodeling, and consolidation, in the diagnosis of pseudoarthrosis and chronic osteomyelitis, bone tumor. The pre-processing of the images was performed using the FLIR tools 6.4 software to extract the temperatures of the regions of interest. Data analysis was performed with MATLAB® 2019a software using a custom-made script. The results showed a thermal difference of 0.9 °C for the presence of the diagnosis of bone fractures and of 2.0 °C for screening for the diagnosis of bone tumor. Cut-off values of 29.72 °C were established for the diagnosis of chronic tibial pseudarthrosis and 33.94 °C for the diagnosis of chronic tibial osteomyelitis. The value of 32.0 °C was established for the thermal profile of reference of the lower limbs and the new protocol for acquiring thermographic images in the supine position was validated. This work showed that infrared thermography can be useful as a complementary diagnostic test for the evaluation of trauma and bone injuries.